Proceso de biodegradación para el tratamiento de derrames de petróleo por medio de pseudomonas (2018)
This monograph was conducted with the objective of broadly describing the process of petroleum biodegradation through Pseudomonas, to demonstrate that despite the fact that the oil industry has had a bad reputation throughout history as a critical focus of environmental pollution, it has investigated and developed methods that help in the cleaning of those fluids that are exposed to the environment during the phases of exploration, exploitation, drilling, production, refining, distribution and consumption, degrading them through biological processes, specifically, the metabolic process that bacteria carry out when digesting Petroleum.